2019
DOI: 10.1139/apnm-2018-0876
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in psychosocial and cardiometabolic health among patients completing cardiac rehabilitation

Abstract: Current programs of cardiac rehabilitation (CR) typically provide a standardized approach to all patients. We examined whether CR would produce similar improvements in psychosocial and cardiometabolic health indicators in women compared with men. The records of patients who completed a 3-month outpatient CR program were examined. We compared health-related quality of life (i.e., Physical Component Summary (PCS) and Mental Component Summary (MCS) scores), anxiety, depression, and cardiometabolic health indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 41 publications
5
36
0
1
Order By: Relevance
“…Consistent with literature [ 49 , 50 ], women did come to CR with a poorer clinical profile than men. Women presented with poorer functional capacity, and had a poorer risk factor profile, but then they do have more to gain.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with literature [ 49 , 50 ], women did come to CR with a poorer clinical profile than men. Women presented with poorer functional capacity, and had a poorer risk factor profile, but then they do have more to gain.…”
Section: Discussionsupporting
confidence: 89%
“…To date, studies investigating sex differences in lipid management during CR have included patients primarily when the AHA/ACC lipid management guidelines recommended an LDL-C target goal of <100 mg/dL using statin therapy (<70 mg/dL for high-risk patients). 77–79 Approximately 50 to 65% of patients met this LDL-C target goal at CR entry, with large cohort studies (n=8929–117 913) reporting that LDL-C decreased by 14 to 35 mg/dL (reductions of ≈15%–36%) following CR 78,79,106 (with smaller cohort studies reporting smaller or no changes in LDL-C 95–97,99,108,109 ). At CR entry, females were less likely to be at the LDL-C target goal compared with males and are reported to have a lower or similar frequency of meeting the LDL-C target goal at CR completion than males.…”
Section: Sex Differences In the Core Components Of Crmentioning
confidence: 99%
“…103 As attending CR programming is associated with greater medication adherence/compliance (with a CR session dose response relationship present), 104,105 CR attendance may minimize these sex differences in high-intensity statin use. Recently, Lin et al 106 78,79,107 (with smaller cohort studies reporting smaller or no changes in LDL-C [95][96][97]99,108,109 ). At CR entry, females were less likely to be at the LDL-C target goal compared with males and are reported to have a lower or similar frequency of meeting the LDL-C target goal at CR completion than males.…”
Section: Lipid Managementmentioning
confidence: 99%
“…A recent women-only HIIT study by Reed et al demonstrated greater clinically meaningful mental health improvements with HIIT when compared to moderate-tovigorous intensity continuous exercise [2]. Further, Terada et al found that women in CR experienced greater reductions in anxiety severity (as assessed by the Hospital Anxiety and Depression Scale) with HIIT (− 1.7 ± 2.7 vs. -0.4 ± 2.8 points, p = 0.036) when compared to men; yet men had larger improvements with moderateto-vigorous intensity continuous exercise [23]. This provides promising evidence for the use of HIIT for women and underscores the importance of formally examining the impact of such programs for cardiac patients.…”
Section: Introductionmentioning
confidence: 99%